Collected conference papers describing remote sensing application projects using the microBRIAN image processing system. (Technical memorandum (Institute of Natural Resources and Environment. Division of Water Resources) ;, 1989)
This Technical Memorandum collects together eight conference papers delivered by members of the CSIRO Division of Water Resources (Canberra Laboratory; formerly called Division of Water and Land Resources) which demonstrate the integration of remote sensing and ancillary data in a range of resource analysis applications. All these projects used the microBRIAN system for image processing and incorporating vector data into raster image channels.